Hydrogen-free defects in hydrogenated black TiO2. Issue 30 (2nd July 2018) - Choi, Heechae; Moon, Seong-I; Song, Teaseup; Kim, Seungchul
Abstract : A hydrogen-free defect in the bulk TiO2 is newly proposed that can exist in hydrogenation condition and can account for most of unique properties of black TiO2 such as high electric conductivity and light absorption spectra. Abstract : Black anatase TiO2 has surprisingly enhanced solar energy harvesting efficiency and electrical conductivity, which makes it a promising material in a wide range of energy and environmental applications. Several experimental and theoretical studies have successfully revealed the mechanisms of band gap reduction by surface hydrogenation of anatase TiO2 . However, recent experimental evidence suggests the existence of bulk point defects that yield infrared (∼1.0 eV) photoabsorption and high conductivity of black anatase TiO2 . In the current study, using a combination of ab initio molecular dynamics simulations and electronic structure calculations, we successfully explain the physical properties, metallicity, and infrared/microwave absorption ( i.e., black color) of highly reduced anatase TiO2 crystal in a hydrogenated state with a newly found pair defect (Tii –VO ) 4+ . Hydrogen atoms in the bulk are unnecessary to understand the observed properties.